2013
DOI: 10.3109/14767058.2013.845156
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic growth factors in maternal and fetal serum in concordant and discordant twin pregnancies

Abstract: Mothers of discordant twins have a more anti-angiogenic environment compared to those of concordant twins. We also found an anti-angiogenic environment in the small twin when we compared umbilical vein angiogenic factors against its big co-twin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…This investigation is one of the largest studies of sFlt‐1 and PlGF levels in twin pregnancies to date, and only a few studies have compared sFlt‐1 and PlGF in twin pregnancies with and without PE. Our findings therefore have important implications for clinical practice for the diagnosis of suspected PE in twin pregnancies.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This investigation is one of the largest studies of sFlt‐1 and PlGF levels in twin pregnancies to date, and only a few studies have compared sFlt‐1 and PlGF in twin pregnancies with and without PE. Our findings therefore have important implications for clinical practice for the diagnosis of suspected PE in twin pregnancies.…”
Section: Discussionmentioning
confidence: 84%
“…A possible pathophysiological explanation for the higher sFlt-1 and PlGF levels in our cohort of twin pregnancies with PE, in comparison with singleton pregnancies with PE, might be the higher placental mass that occurs in twin pregnancies 25 . A direct correlation between placental weight and levels of angiogenic factors is still a topic of controversy 26,27 . Furthermore, maternal blood volume is altered in twin pregnancies compared to singleton ones; an elevated extracellular volume in twin pregnancies might lead to different concentrations of serum factors in twins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin pregnancies have an increased risk of developing PE per se , and may have different cut‐offs for the diagnosis of the disease. In many studies it has been found that the levels differ in twin compared with singleton pregnancies and appropriate cut‐off values need to be determined. Similarly , the reported sensitivities and specificities in the presented studies are specific for the study populations, which may not reflect each and every single ethnicity and region in the world.…”
Section: Prediction Of Diseasementioning
confidence: 99%
“…1820 The timing of these changes in angiogenic balance may provide insight into the mechanism whereby preeclampsia risk is elevated in women carrying multiple gestations. Therefore, we followed women longitudinally through pregnancy and delivery to examine circulating maternal concentrations of placental growth factor (PlGF), sFlt-1, and s-endoglin in twin and singleton pregnancies.…”
Section: Introductionmentioning
confidence: 99%